Requirement for a second sterol biosynthetic mutation for viability of a sterol C-14 demethylation defect in Saccharomyces cerevisiae. - Taylor, F R (1983)
Genetic analysis of a nystatin-resistant sterol mutant (strain JR4) of Saccharomyces cerevisiae defective in C-14 demethylation revealed the presence of a second mutation in 5,6-desaturation. It appeared from complementation tests that a defect in delta 5-desaturase enzyme activity was required for the viability of the C-14 demethylation mutant. Growth studies with a sterol auxotrophic strain indicated that the major sterol of strain JR4, 14 alpha-methyl-ergosta-8,24(28)-dien-3 beta-ol, could satisfy "bulk" membrane requirements but not the second, structurally specific, sterol function that we defined previously (Rodriguez et al., Biochem. Biophys. Res. Commun. 106:435-441, 1982). Leakiness in the sterol mutations in strain JR4 provided a small amount of ergosterol which could satisfy this second function.